1924. Outpatient Treatment With the SARS-CoV-2–Neutralizing Antibody Combination AZD7442 (Tixagevimab/Cilgavimab) for Preventing COVID-19 Hospitalizations in the Phase 3 TACKLE Trial. (15th December 2022) - Richard Hobbs, F D; Montgomery, Hugh; Padilla, Francisco; Kim, Kenneth; Simón Campos, Jesus Abraham; Arbetter, Douglas; Padilla, Kelly W; Reddy, Venkatesh P; Seegobin, Seth; Streicher, Katie; Viani, Rolando M; Koh, Gavin C KW; et al.
Abstract: Background: Outpatient treatment with SARS-CoV-2–neutralizing antibody combination AZD7442 (tixagevimab/cilgavimab) in adults with mild to moderate COVID-19 significantly reduced progression to severe disease or death through Day 29 and was well-tolerated in the Phase 3 TACKLE study primary analysis (NCT04723394). AZD7442 administered earlier in the disease course leads to more favorable outcomes and has the potential to prevent COVID-19 hospitalizations and reduce hospital burden. We report key secondary efficacy results with longer-term safety data from TACKLE over 6 months. Methods: In TACKLE, non-hospitalized adults with mild to moderate COVID-19 were randomized 1:1 and dosed ≤7 days from symptom onset with a single 600-mg AZD7442 dose (2 consecutive intramuscular injections, 300 mg of each antibody; n=452) or placebo (n=451). The key secondary endpoint was death from any cause or hospitalization for COVID-19 complications or sequelae through Day 169, analyzed using a Cochran-Mantel-Haenszel test stratified by time from symptom onset and risk of severe COVID-19 progression. Results: Death from any cause or hospitalization for COVID-19 complications or sequalae occurred in 20 (5.0%) versus 40 (9.8%) participants receiving AZD7442 versus placebo, respectively, translating to a relative risk reduction (RRR) of 49.1% (95% confidence interval [CI] 14.5–69.7) versus placebo (P=0.009). A sensitivity analysis excluding participants who were unblinded prior to Day 169 for consideration of vaccination yielded a similar RRR of 50.7% (95% CI 17.5–70.5; P=0.006). For baseline seronegative participants, an RRR of 58.6% (95% CI 27.6–76.4; P=0.001) was observed. The median (range) safety follow-up was 170 (1–330) days with AZD7442 and 170 (1–326) days with placebo. Adverse events occurred in 38.5% of AZD7442 participants and 43.5% of placebo participants, and were mostly mild to moderate. Conclusion: A single 600-mg AZD7442 dose demonstrated statistically significant protection against death from any cause or hospitalization for COVID-19 through 6 months, and was well-tolerated. These data provide further support of AZD7442 in the COVID-19 outpatient treatment setting, with potential to reduce hospital burden. Disclosures: F.D. Richard Hobbs, FMedSci, AstraZeneca: Grant/Research Support|AstraZeneca: Principal investigator|NIHR Applied Research Collaboration, Oxford Thames Valley: Director|Oxford BRC and NIHR MedTech: Investigator|UKRI and NIHR: Grant/Research Support Hugh Montgomery, MD, AstraZeneca: Advisor/Consultant|Millfield Medical Ltd: Advisor/Consultant|UK National Institute for Health Research's Comprehensive Biomedical Research Centre at University College London Hospitals: Grant/Research Support Francisco Padilla, MD, Amgen: Grant/Research Support|Amgen: Personal fees|AstraZeneca: Grant/Research Support|AstraZeneca: Personal fees|Boehringer Ingelheim: Grant/Research Support|Boehringer Ingelheim: Personal fees|Ferrer: Grant/Research Support|Ferrer: Personal fees|Kowa: Grant/Research Support|Kowa: Personal fees|Medix: Grant/Research Support|Medix: Personal fees|Merck Sharp and Dohme: Grant/Research Support|Merck Sharp and Dohme: Personal fees|Novartis: Grant/Research Support|Novartis: Personal fees|Pfizer: Grant/Research Support|Pfizer: Personal fees|Sanofi: Grant/Research Support|Sanofi: Personal fees|Servier: Grant/Research Support|Servier: Personal fees|Silanes: Grant/Research Support|Silanes: Personal fees Kenneth Kim, MD, Adagio: Funding|Eli Lilly: Funding|Merck: Funding|Pfizer: Funding|Regeneron: Speaker|Regeneron: Funding Jesus Abraham Simón Campos, MD, AstraZeneca: Board Member|AstraZeneca: Speaker|Eli Lilly: Board Member|Pfizer: Board Member|Roche: Board Member|Roche: Speaker Douglas Arbetter, MPH, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Kelly W. Padilla, PharmD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Venkatesh P. Reddy, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Seth Seegobin, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Katie Streicher, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Rolando M. Viani, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Gavin CKW Koh, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Mark T. Esser, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds.